A latent profile analysis of EFL learners' self-efficacy: Associations with academic emotions and language proficiency. (December 2021) - Wang, Yabing; Shen, Bin; Yu, Xiaoxiao
Abstract: While self-efficacy has been constantly related to language learning outcomes, so far, no study, to the best of our knowledge, has investigated whether self-efficacy profiles are associated with academic emotions and language proficiency among Chinese English-as-a-foreign-language (EFL) undergraduates. This study aimed to identify self-efficacy profiles using a person-centered latent profile analysis (LPA) and explore their relationships with academic emotions and language proficiency. Three hundred non-English major undergraduates from two universities in China completed the questionnaires measuring their self-efficacy beliefs, academic emotions and language proficiency in a national standardized test. The LPA results identified three groups representing low, medium and high self-efficacy levels. Students with high level of self-efficacy experienced the most pleasant emotions (enjoyment, pride), the least unpleasant emotions (anger, anxiety, and shame), and scored highest in overall language test, as well as the listening and reading subtests. Those in the low and medium self-efficacy groups showed differences in most measures of academic emotions but not in language proficiency. This study could enhance the understanding of Chinese EFL undergraduates' self-efficacy patterns and offer new insights into English language instruction practice. Highlights: Students demonstrated different profiles of self-efficacy in English learning. Profiles of self-efficacy were associated with academic emotions and language proficiency. The associations between self-efficacy, academic emotions and language proficiency depended on profiles of self-efficacy and language skill.